Prevalencia de la caries de dentina y necrosis pulpar en pacientes de 20 a 39 años, de la población atendida en la Unidad Anidada Hospital Básico Macará – Ecuador - 2018 - Ludeña Salinas, Anabel Carolina (2022)
Dental caries present high levels of prevalence worldwide and nationally; we consider it a real problem in public health since it is a multifactorial lesion that can begin at an early age and continue throughout life. If not treated, it can evolve and eventually present complications, while we consider pulp necrosis as the death of the dental pulp caused mainly by the progression of carious lesions. We developed the current research work to determine the prevalence that exists of dentin caries and pulp necrosis in Ecuadorian patients between 20 to 39 years old, were attended at Unidad Anidada Hospital Básico de Macará during the year 2018 reason why this study was observational, descriptive, retrospective, and transversal, because of that, we characterized it by the analysis of the original Exportado de RDACCA-2018, provided by the MSP. The results showed a high prevalence of dentin caries, represented by 77.2%, corresponding to 505 of the evaluated data, where there was a higher prevalence in the female sex with 81.19% (n-410). And regarding age, there was a higher prevalence in the 24 years old group with 9.90% (n-50), while pulp necrosis presented a low prevalence, which we represented by 22.8% (n=149) in terms of sex, there was also a greater predilection for the female sex with 76.51% (n=114), and finally, concerning age, the group with the highest prevalence was 24 years of age represented with 13.42% (n=20). Therefore, there was a high prevalence of dentin caries and a low prevalence of pulp necrosis in the present study group